"Made in Country" Versus "Made in County": Effects of Local Manufacturing Origins on Price Perceptions. Issue 2 (10th January 2013) - Suri, Rajneesh; Thakor, Mrugank V.
ABSTRACT Consumers often use an array of extrinsic and intrinsic attributes to infer product quality and to assess monetary sacrifice. However, literature reveals little about how and if consumers would use information on product's manufacturing origins differently if it was national rather than local. In two studies, the role played by uncertainty in judgments of the quality of locally made products is examined. It is shown that when consumers are motivated to process information and quality ratings are high, local identity effects are elicited and monetary sacrifice perceptions are diminished. These results suggest that favorable quality ratings need to be prominently featured when promoting locally made products, and that locally made products are preferred to national ones only when quality is not a concern.